Teachers’ Attitudes Towards Educational Philosophy and Multicultural Education - Bucea (Rusu), Rodica Paraschiva (Didactica Danubiensis, 2025)
This article explores the interplay between the educational philosophies adopted by teachers and their attitudes towards multicultural education. The study reveals how philosophical orientations influence the willingness and ability of teachers to embrace diverse cultural perspectives in their teaching practices. The theoretical framework highlights significant connection between educational philosophies and multicultural education, offering insights into how teacher preparation programs can align their curricula with the principles of equity and inclusion to foster culturally responsive teachers.